UNEXPECTED EXTRAPYRAMIDAL REACTION: ACUTE TARDIVE DYSKINESIA FOLLOWING SHORT-TERM METOCLOPRAMIDE USE IN A PATIENT WITH DIABETES AND CHRONIC KIDNEY DISEASE - Helmizar, Roland; Yuri Haiga; Vina Tri Septiana; Nana Liana; Ruhsyahadati Ajisman; Rahma Triyana; Muhammad Rizki Saputra (Nusantara Hasana Journal, 2025)
Tardive dyskinesia (TD) is a potentially irreversible extrapyramidal movement disorder characterized by involuntary, repetitive movements, predominantly affecting the orofacial region. Although most commonly associated with prolonged exposure to dopamine receptor–blocking agents, TD may also arise following the use of gastrointestinal prokinetics such as metoclopramide. Female sex, diabetes mellitus, advanced age, and renal impairment are recognized risk factors that increase susceptibility, yet TD remains underrecognized outside psychiatric settings. A 49-year-old woman with poorly controlled type 2 diabetes mellitus presented with nausea, vomiting, and generalized weakness. Laboratory findings demonstrated normocytic anemia, uncontrolled hyperglycemia (HbA1c 9.2%), and acute-on-chronic kidney disease (eGFR 22 mL/min/1.73 m²). She received standard supportive therapy, including intravenous metoclopramide. Within 24 hours, she developed repetitive tongue protrusion and orofacial dyskinesia. Neuroimaging and electrolyte evaluation were unremarkable, and there was no history of prior neuroleptic exposure. Metoclopramide was promptly discontinued, leading to gradual improvement and complete resolution of symptoms within two weeks. Antiemetic therapy was switched to ondansetron. This case underscores that acute TD may occur after short-term metoclopramide use, particularly in patients with diabetes and renal dysfunction. Heightened clinical awareness and cautious prescribing are essential to prevent this potentially disabling adverse effect.